Thermodynamic and experimental investigation of solar-driven biomass pyro-gasification using h2o, co2, or zno oxidants for clean syngas and metallurgical zn production - Chuayboon, Srirat; Abanades, Stéphane (My University, 2021)
The solar gasification of biomass represents a promising avenue in which both renewable solar and biomass energy can be utilized in a single process to produce synthesis gas. The type of oxidant plays a key role in solar-driven biomass gasification performance. In this study, solar gasification of beech wood biomass with different oxidants was thermodynamically and experimentally investigated in a 1.5 kWth continuously-fed consuming bed solar reactor at 1200◦C under atmospheric pressure. Gaseous (H2O and CO2 ) as well as solid (ZnO) oxidants in pellet and particle shapes were utilized for gasifying beech wood, and the results were compared with pyrolysis (no oxidant). As a result, thermodynamic predictions provided insights into chemical gasification reactions against oxidants, which can support experimental results. Compared to pyrolysis, using oxidants significantly promoted syngas yield and energy upgrade factor. The highest total syngas yield (63.8 mmol/gbiomass ) was obtained from biomass gasification with H2O, followed by CO2, ZnO/ biomass mixture (pellets and particles), and pyrolysis. An energy upgrade factor (U) exceeding one was achieved whatever the oxidants, with the maximum U value of 1.09 from biomass gasification with ZnO, thus highlighting successful solar energy storage into chemical products. ZnO/biomass pellets exhibited greater gas yield, particularly CO, thanks to enhanced solid–solid reaction. Solid product characterization revealed that ZnO can be reduced to high-purity Zn through solar gasification, indicating that solar-driven biomass gasification with ZnO is a promising innovative process for CO2-free sustainable co-production of metallic Zn and high-quality syngas.
Keywords: Biomass; Chemical looping gasification; Metal oxide; Metallurgy; Solar reactor; Thermochemical conversion